Evaluación de la Estrategia de Nivelación en Física, Química y Matemática (ENFIQUIMA) en la Universidad Estatal a Distancia de Costa Rica, durante el período 2021- 2022 (Revista Electrónica Calidad en la Educación Superior, 2023)
The disassociation between the secondary education academic level and the one required for university education has brought difficulties for students and produced desertion. The leveling subjects aim to strengthen the previous knowledge of students, to improve academic success and reduce desertion in the following courses. In this work, we describe the Leveling Strategy in Physics, Chemistry and Mathematics (ENFIQUIMA, for its acronym in spanish), with the purpose of evaluating it from a student’s perspective, academic performance and a FODA analysis to look for improvement areas. In this research quantitative and qualitative data were used, for a mixed, concurrent type, and an exploratory-descriptive reach. To evaluate the ENFIQUIMA, the research group used: a) a diagnosis of 286 students enrolled in Physics, Chemistry and Mathematics courses´ perceptions about the ENFIQUIMA. b) an analysis of the academic performance of 119 students that passed nivelatory courses. c) a FODA analysis of the ENFIQUIMA. It was determined that 89% (255) of the students enrolled in in Physics, Chemistry and Mathematics courses did not know nivelatory courses were available. The effectivity of the ENFIQUIMA was confirmed in the Chemistry course. The Physics and Mathematics courses could not be evaluated because of a small number of students with the criteria of an excessive number of courses following the nivelatory. Most students in the courses Physics I, Chemistry I and Mathematics are unaware of the existence of the ENFIQUIMA and most students that passed the nivelatory and also the next course consider the ENFIQUIMA benefited them. In Chemistry, the success rate in students that passed the nivelatory course was double the rate of those that didn’t. Areas of improvement for the ENFIQUIMA were identified.
Keywords: academic performance; desertion; strategy; leveling